A Critical Analysis of Disability Policy and Practice in Flanders: Toward Differentiated Manifestations of Interdependency. Issue 2 (18th February 2020) - Roets, Griet; Dermaut, Vanessa; Benoot, Toon; Claes, Claudia; Schiettecat, Tineke; Roose, Rudi; Van Lancker, Wim; Vandevelde, Stijn
Abstract: Notions of citizenship and disability rights denote abstract, ambiguous, and contested principles, and realizing these ideas entails complexity in practice. This is particularly the case since the welfare state is no longer conceived as the principal provider of welfare services and resources in many European welfare states. In that vein, we critically analyze the underlying principles, rationales, values, and potential implications of the White Paper "Perspective 2020: a new support policy for disabled people" in Flanders (the Dutch speaking part of Belgium). We tease out which understanding of the disabled human subject is promoted by this so‐called innovative social policy and excavate how policy makers and a diversity of actors involved in the policy implementation process consider the provision of care and support. Our main argument entails that the welfare state should acknowledge and vindicate differentiated manifestations of interdependency rather than reinforcing a dichotomy that is based on notions of in/dependent human subjects.